DAMPAK INTENSITAS PENGGUNAAN MEDIA SOSIAL TERHADAP KARAKTER SANTRI DI PONDOK PESANTREN MIFTAHUL HUDA MALANG - Afrizal Pradana; Muhammad Dzikrullah Hanafi; Moch Sulthoni Faizin (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2020)
Dependence on using social media can have an impact on the character of students. Santri at the Miftahul Huda Islamic boarding school in Malang are one of the people who often use it. The results of this study prove that the intensity of the use of social media by students at the Islamic boarding school Miftahul Huda Malang is quite high. The intensity of the use of social media has a negative impact on the character of the students at Islamic boarding school Miftahul Huda Malang. However, specifically for the character of students towards teachers, the intensity of using social media did not really have an impact. Based on the results of observations, it was found that the intensity of the use of social media by students in Islamic boarding school Miftahul Huda Malang was very high. It was also found that the intensity of the use of social media has a negative impact on the character of the students at the Miftahul Huda Islamic boarding school in Malang. In other words, the high intensity of social media use resulted in a negative impact on the character of students for themselves, teachers and lessons at Islamic boarding school Miftahul Huda Malang.